2016
DOI: 10.12688/f1000research.9629.1
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial apoptosis and BH3 mimetics

Abstract: The BCL2-selective BH3 mimetic venetoclax was recently approved for the treatment of relapsed, chromosome 17p-deleted chronic lymphocytic leukemia (CLL) and is undergoing extensive testing, alone and in combination, in lymphomas, acute leukemias, and solid tumors. Here we summarize recent advances in understanding of the biology of BCL2 family members that shed light on the action of BH3 mimetics, review preclinical and clinical studies leading to the regulatory approval of venetoclax, and discuss future inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 120 publications
0
36
0
Order By: Relevance
“…Sirtinol also reversed salidroside‐resulted in the decreases in apoptotic cell number and apoptotic rate under MPP + condition (Figures C and 3D). Bcl‐2 family member play an important role in mitochondrial apoptosis (Dai et al, ). We further found that salidroside mitigated MPP + ‐induced the increased Bax (pro‐apoptotic protein)/Bcl‐2 (anti‐apoptotic protein) ratio in SH‐SY5Y cells (Figures E and 3F).…”
Section: Resultsmentioning
confidence: 99%
“…Sirtinol also reversed salidroside‐resulted in the decreases in apoptotic cell number and apoptotic rate under MPP + condition (Figures C and 3D). Bcl‐2 family member play an important role in mitochondrial apoptosis (Dai et al, ). We further found that salidroside mitigated MPP + ‐induced the increased Bax (pro‐apoptotic protein)/Bcl‐2 (anti‐apoptotic protein) ratio in SH‐SY5Y cells (Figures E and 3F).…”
Section: Resultsmentioning
confidence: 99%
“…Direct and specific inhibitors against Mcl‐1 are so far lacking. The progress in the search of small compounds, selective against Mcl‐1, is summarized in recently published reports . Mcl‐1 plays a central role in chemoresistance to anti‐tubulin agents as vincristine.…”
Section: Targeting Mitochondria In Therapy Of T‐allmentioning
confidence: 99%
“…And we believe that Caspase-3 participates in the cordycepin induced apoptosis in CCA. Moreover, the Bcl-2 family is the key mediator of the intrinsic (mitochondrial) pathway, which includes some of the most extensive-studied proteins, such as Bcl-2, the antiapoptotic protein, Bax, the pro-apoptotic protein [22]. The ratio of Bcl-2/Bax is usually used to assess the occurrence of apoptosis.…”
Section: Discussionmentioning
confidence: 99%